PROFESSIONAL TRAINING OF FUTURE BACHELORS IN INTERNATIONAL LAW AT A TECHNICAL INSTITUTION OF HIGHER EDUCATION - Markelov, Andrii (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2024)
The article reveals the theoretical and practical aspects of the professional training of future bachelors in international law. The educational and professional program "International Law" of the first (bachelor’s) level of higher education was analyzed; the concepts of "educational environment", "educational environment of a higher education institution" have been clarified; it was established that the educational environment of a higher education institution is a whole that encompasses a set of conditions, influences, opportunities for professional training, personality development, and socialization of a future specialist. An analysis of the skills of a modern specialist, in demand on the modern labor market, was carried out: digital literacy; data literacy; critical thinking; emotional intelligence; creativity; cooperation; flexibility; leadership qualities; self-management; self development. The structure of the innovative educational environment of the university from the standpoint of organizational and managerial activity is presented. The given structure constitutes the optimal environment for the training of bachelors in international law, where the "Content of the educational process" component includes the organization and control of the educational process, tracking of state policy and the regulatory environment that it defines; taking into account trends in the world and domestic markets; provision of a regulatory documentation base for all components of the educational environment, the functioning of which it directly determines. Management forecasting and risk assessment: marketing; and analysis of the labor market, knowledge of production and educational services; determine the potential of the university, as well as short-term and long-term forecasting of the conditions of its economic and educational activity; determine directions of expansion of the spectrum of activities; carry out an assessment of possible risks and find out ways to reduce their level. Adjustment of the content of the OPP "International Law", educational and methodological base